Pengaruh Model Pembelajaran Contextual Teaching Learning (CTL) Terhadap Minat Belajar IPA Siswa Kelas IV UPTD SD Negeri 122353 Pematang Siantar - Sonia Raherka; Muktar Panjaitan; Emelda Thesalonika Manalu (Journal on Education, 2023)
The purpose of the research is to achieve learning and educational goals and, as well as foster student interest in learning. This type of research is quantitative, with the correlation method. The population in this study is all fourth grade elementary school (SD) students consisting of 30 students, the number of research instruments used is a questionnaire to determine the effect of the Contextual Teaching Learning ( CTL ) Model on the Science Learning Interest of Grade IV Students UPTD SD Negeri 122353 PematangSiantar With a questionnaire of 25 questions. Based on the results of this study indicate that the influence of the Contextual Teaching Learning (CTL) learning model on students' interest in learning science. The results of the research data analysis showed that the correlation was proven by the value of rcount = 0.883>0.361 and it could be concluded that there was an effect of the Contextual Teaching Learning (CTL) learning model on students' interest in science learning in class IV UPTD SD Negeri 122353 Pematang Siantar.